2008
DOI: 10.1016/j.febslet.2008.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Oxidised LDL up‐regulate CD36 expression by the Nrf2 pathway in 3T3‐L1 preadipocytes

Abstract: The effect of oxLDL on CD36 expression has been assessed in preadipocytes induced to differentiate. Novel evidence is provided that oxLDL induce a peroxisome proliferator-activated receptor c-independent CD36 overexpression, by up-regulating nuclear factor erythroid 2 (NF-E2)-related factor 2 (Nrf2). The nuclear translocation of Nrf2 appeared to depend on PKC pathway activation. In adipocytes, the CD36 up-regulation may indicate a compensation mechanism to meet the demand of excess oxLDL and oxidised lipids in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
35
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 37 publications
7
35
0
1
Order By: Relevance
“…This was related to the PPARg activation due to thiazolidinedione. What makes the present study different is that in our system PPARg was not activated, but oxLDL decreased its level also in agreement with our previous papers (56). Summarizing, we provided evidence that oxLDL lowered the sensitivity of adipocytes to insulin by impairing GLUT4 translocation and glucose uptake.…”
Section: Oxldl Impair Insulin Signaling In Adipocytes 839supporting
confidence: 78%
See 1 more Smart Citation
“…This was related to the PPARg activation due to thiazolidinedione. What makes the present study different is that in our system PPARg was not activated, but oxLDL decreased its level also in agreement with our previous papers (56). Summarizing, we provided evidence that oxLDL lowered the sensitivity of adipocytes to insulin by impairing GLUT4 translocation and glucose uptake.…”
Section: Oxldl Impair Insulin Signaling In Adipocytes 839supporting
confidence: 78%
“…We have recently demonstrated that oxLDL can be actively taken up by 3T3-L1 preadipocytes through a CD36-mediated transport and that they can induce a significant increase in membrane receptor content. This enables oxLDL to interfere with the homeostasis of adipose tissue by altering the normal balance between differentiation and proliferation in preadipocytes, thus potentially contributing to the appearance of insulin resistance (55,56). Furthermore, oxLDL are a causative factor in lowering insulin sensitivity in cultured cells, possibly by inhibiting the signaling kinases responsible for the cellular response to insulin (57) and/or by activating the NF-kB complex, responsible for the regulation of genes involved in inflammation and cell survival (58).…”
mentioning
confidence: 99%
“…A chronic inhibitory effect of apoB-lipoproteins/LDL was revealed ex vivo and in vitro as i ) plasma apoB was inversely related to in situ LPL activity and NEFA storage in women's WAT and ii ) LDL-differentiated 3T3-L1 adipocytes had decreased in situ LPL activity and NEFA storage. In addition, LDL had a direct acute inhibitory effect on TRL clearance as i ) LDL treatment of WAT for 4 h reduced the hydrolysis of synthetic TRL and increased the accumulation of LPL-derived to bind and be internalized by CD36 in mouse 3T3-L1 cells, causing the upregulation of preadipocyte factor-1 (Pref-1), whose suppression is key for the expression of peroxisome proliferator-activated receptor ␥ and adipocyte differentiation (21)(22)(23). Although higher oxidized LDL levels are likely more abundant in women with high apoB and their effects on adipocytes function cannot be excluded; our data demonstrate that LDL taken from women with both low and high apoB induced equivalent negative effects on WAT function ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms responsible for delayed plasma clearance of postprandial TRL by WAT are not fully understood. However, the uptake of LDL, albeit oxidized, by 3T3-L1 adipocytes was reported to increase cell proliferation and decrease cell differentiation (21)(22)(23). Moreover, multiple clinical studies have demonstrated that statin therapy, which reduces plasma concentrations of apoBlipoproteins, also improves plasma clearance of triglyceride (TG) (24)(25)(26)(27).…”
Section: Postprandial In Vivo Fat Clearancementioning
confidence: 99%
“…A study reported that hyperinsulinemia and impaired glycaemic control independent of lipid level were associated with increased in vivo LDL oxidation, as reflected by the higher prevalence of highly oxidized LDL [5]. Ox-LDL is reported to interfere with the homeostasis of adipose tissue by altering the normal balance between differentiation and proliferation in preadipocyte, which potentially contributes to the appearance of insulin resistance [38].…”
Section: Discussionmentioning
confidence: 99%